A A new combination in Mucuna (Leguminosae-Phaseoleae) of Florae Fluminensis - Menezes, Helen F. De; Pastore, José Floriano B. (Phytotaxa, 2023)
The name Dolichos pungens, described in Vellozo’s Florae Fluminensis, is here revised and transferred to the genus Mucuna, as M. pungens. Expeditions were conducted to the probable original locality of Dolichos pungens in Paraty, a municipality in the state of Rio de Janeiro, Brazil, accompanied by the revision of herbarium specimens. A comprehensively species description, distribution map, and taxonomic notes are provided. A lectotype has been designated for Dolichos pungens.